(untitled) (American Journal of Arts and Human Science, 2024)
From the perspective of Chinese and Western urban aesthetics, the article studied 15 existing scientific literature sources in terms of building types, building scale, gardening art, the relationship between gardens and architecture, the aesthetic style of castles and buildings, artistic origins, and aesthetic tastes. Using the classification and comparative analysis method, the artistic characteristics of Chinese and Western classical gardens were compared, the reasons for the differences in the artistic characteristics of Chinese and Western classical gardens were analyzed, and it was pointed out that the integration of Eastern and Western garden arts has reference significance for Chinese urban greening.